Controlled Covalent Functionalization of Thermally Reduced Graphene Oxide To Generate Defined Bifunctional 2D Nanomaterials. (6th February 2017) - Faghani, Abbas; Donskyi, Ievgen S.; Fardin Gholami, Mohammad; Ziem, Benjamin; Lippitz, Andreas; Unger, Wolfgang E. S.; Böttcher, Christoph; Rabe, Jürgen P.; Haag, Rainer; Adeli, Mohsen
Abstract: A controlled, reproducible, gram‐scale method is reported for the covalent functionalization of graphene sheets by a one‐pot nitrene [2+1] cycloaddition reaction under mild conditions. The reaction between commercially available 2, 4, 6‐trichloro‐1, 3, 5‐triazine and sodium azide with thermally reduced graphene oxide (TRGO) results in defined dichlorotriazine‐functionalized sheets. The different reactivities of the chlorine substituents on the functionalized graphene allow stepwise post‐modification by manipulating the temperature. This new method provides unique access to defined bifunctional 2D nanomaterials, as exemplified by chiral surfaces and multifunctional hybrid architectures.